Prevalence of Clostridium difficile and Salmonella spp in juvenile dogs with parvoviral enteritis and clinically healthy controls - Annandale, C.H. (Cornelius Henry) (University of Pretoria, 2018)
Dissertation (MMedVet)--University of Pretoria, 2018.